2017
DOI: 10.22186/jyi.33.1.8-18
|View full text |Cite
|
Sign up to set email alerts
|

Is Unpaved Road Dust Near Fairbanks, Alaska a Health Concern? Examination of the Total and Bioaccessible Metal(loid)s

Abstract: Recent studies highlight the health risks associated with toxic metal(loid)s [e.g., arsenic (As), zinc (Zn), and lead (Pb)] in dust from mining operations, urban settings, and rural roads. To have a deleterious health effect, inhaled or ingested metal(loid)s must dissolve under conditions in the lung or gastrointestinal tract. In this study, we determined total and physiologically-soluble fractions of metal(loid)s in road dust from four sites in east-central interior Alaska. Total As and antimony (Sb) were enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…Gastric PBET supernatant concentrations of Pb, As, and Sb exceed the EPA DWS by 34×, 14×, and 10×, respectively (EPA 2018). Simulated lung fluid solubilized a smaller fraction of PTEs relative to gastric extractions (except for Se, with 28% liberation), consistent with previous studies (Knight et al 2017;Schaider et al 2007), but still exceeded EPA standards for As and Se by 1.8× and 1.2×, respectively. Taken together, the SPLP and PBET results indicate that additional examination of this FA is warranted because of regulatory exceedances and significant bioavailability of PTEs in this FA.…”
Section: Standard Leaching Experimentssupporting
confidence: 87%
“…Gastric PBET supernatant concentrations of Pb, As, and Sb exceed the EPA DWS by 34×, 14×, and 10×, respectively (EPA 2018). Simulated lung fluid solubilized a smaller fraction of PTEs relative to gastric extractions (except for Se, with 28% liberation), consistent with previous studies (Knight et al 2017;Schaider et al 2007), but still exceeded EPA standards for As and Se by 1.8× and 1.2×, respectively. Taken together, the SPLP and PBET results indicate that additional examination of this FA is warranted because of regulatory exceedances and significant bioavailability of PTEs in this FA.…”
Section: Standard Leaching Experimentssupporting
confidence: 87%
“…Aer an extensive literature review, only a few studies were found that addressed rural unpaved roads; [14][15][16][17][18][19][20] the focus of most of the identied road dust emission research was on urban roads. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] No peer-reviewed research was identied for either rural or urban unpaved roads that evaluated steel slag as a source of fugitive emissions.…”
Section: Introductionmentioning
confidence: 99%